1991
DOI: 10.1007/bf00039661
|View full text |Cite
|
Sign up to set email alerts
|

In vitro production of male sterile Zinnia elegans

Abstract: Axillary bud proliferation of Zinnia elegans Jacq . was accomplished from vegetative bud explants of greenhouse-grown plants . Photoperiod extension via metalarc lamps in the greenhouse stock plant environment significantly increased both the quantity and quality of explants . Shoot cultures initiated from axillary buds of identified male sterile plants proliferated best on a medium with 1 gM BAP . Microshoots exhibited 80% rooting on media without growth regulators, and 100% acclimatization of rooted plantlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…This effect may have been due to the direct result of higher rates of CO 2 assimilation and stomatal conductance in tissue culture raised plants (Cameron et al, 1985). The superiority of in vitro male sterile Zinnia elegans plants over their seed-derived counterparts has also been demonstrated (Rogers et al, 1992). They also found that in vitro produced plants initiated flowers approximately three weeks earlier, with more plants with smaller head size as compared to seedderived plants.…”
Section: Discussionmentioning
confidence: 93%
“…This effect may have been due to the direct result of higher rates of CO 2 assimilation and stomatal conductance in tissue culture raised plants (Cameron et al, 1985). The superiority of in vitro male sterile Zinnia elegans plants over their seed-derived counterparts has also been demonstrated (Rogers et al, 1992). They also found that in vitro produced plants initiated flowers approximately three weeks earlier, with more plants with smaller head size as compared to seedderived plants.…”
Section: Discussionmentioning
confidence: 93%